2021
DOI: 10.1186/s13045-021-01119-w
|View full text |Cite
|
Sign up to set email alerts
|

Quality-adjusted Time Without Symptoms of disease or Toxicity (Q-TWiST) analysis of CPX-351 versus 7 + 3 in older adults with newly diagnosed high-risk/secondary AML

Abstract: Background CPX-351 (United States: Vyxeos®; Europe: Vyxeos® Liposomal), a dual-drug liposomal encapsulation of daunorubicin and cytarabine in a synergistic 1:5 molar ratio, is approved by the US FDA and the EMA for the treatment of adults with newly diagnosed therapy-related acute myeloid leukemia or acute myeloid leukemia with myelodysplasia-related changes. In a pivotal phase 3 study that evaluated 309 patients aged 60 to 75 years with newly diagnosed high-risk/secondary acute myeloid leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…230 The results of clinical trials demonstrated clinical benefits and confirmed CPX-351 as a standard intensive therapy for high-risk or secondary acute myeloid leukemia in older patients. 231 Although nanomedicine has shown inspiring efficacy in preclinical studies, many limitations and difficulties remain in the path of clinical translation. The limited gain in OS has not satisfied clinicians and patients.…”
Section: Clinical Applications Of Nanomedicinementioning
confidence: 99%
“…230 The results of clinical trials demonstrated clinical benefits and confirmed CPX-351 as a standard intensive therapy for high-risk or secondary acute myeloid leukemia in older patients. 231 Although nanomedicine has shown inspiring efficacy in preclinical studies, many limitations and difficulties remain in the path of clinical translation. The limited gain in OS has not satisfied clinicians and patients.…”
Section: Clinical Applications Of Nanomedicinementioning
confidence: 99%
“…In summary, CPX-351 requires optimal management and prophylaxis to mitigate the risk of infections probably related to the more prolonged neutropenia. Mucositis and alopecia are reduced, and this translates to improved quality of life for patients [ 42 ]. One fifth of patients presents skin toxicity that is self-resolving; however, severe cases have been reported [ 43 ].…”
Section: Treatment Toxicitiesmentioning
confidence: 99%
“…Several studies indicated that the treatment with CPX-351 has the ability to produce quality-of-life benefits compared to conventional chemotherapy [ 42 , 44 , 45 , 46 ].…”
Section: Treatment Toxicitiesmentioning
confidence: 99%
See 2 more Smart Citations